Assessment of macular structures and vascular characteristics in highly myopic anisometropia using swept-source optical coherence tomography angiography - Wang, Xin; Chen, Yanhui; Wang, Zhiyang; Li, Haoru; He, Qing; Rong, Hua; Wei, Ruihua (Frontiers in Physiology, 2022)
Abstract Purpose: This study aimed to explore the macular structures and vascular characteristics of more myopic (MM) and contralateral eyes with highly myopic anisometropia. Methods: Comprehensive ophthalmic examinations were performed for 33 patients with highly myopic anisometropia. Macular structures (total retinal layer [TRL], ganglion cell and inner plexiform layer [GCIPL], inner nuclear layer [INL], outer retinal layer [ORL], nerve fiber layer [NFL], choroidal layer [CHL]) and vascular characteristics (superficial vascular complex density [SVD], deep vascular complex density [DVD], choriocapillaris perfusion area [CCPA]) were assessed using swept-source optical coherence tomography (SS-OCT) and OCT angiography (OCTA). Macular structures and vascular characteristics of each subregion were compared to those of the Early Treatment of Diabetic Retinopathy Study (ETDRS). Results: With highly myopic anisometropia, the thicknesses of the TRL, GCIPL, INL, and ORL in MM eyes were smaller than those in contralateral eyes in at least one quadrant of the perifoveal and parafoveal circles (all P < 0.05), with no changes in the foveal and temporal quadrants of perifoveal regions (all P > 0.05). A thicker NFL (P = 0.018) was found in MM eyes than in contralateral eyes in the superior perifoveal quadrant. The CHL (all P < 0.05) in MM eyes was thinner in all regions than in the contralateral eyes according to the ETDRS. There were no statistical differences in the SVD, DVD, and CCPA of MM and contralateral eyes (all P > 0.05). Conclusion: All retinal layers, except the RNFL, tended to be thinner in all subregions, except the temporal perifoveal and foveal quadrants in MM eyes, and choroidal thickness was thinned in all areas.